Empowering Adolescent Health Cadres through Peer Counselor Training to Prevent Early Marriage in Village X - Fatimah, Fatimah; Siregar, Rahma Juliani; Harahap, Maryam Latifah (PT Inovasi Pratama Internasional, 2026)
Early marriage remains a critical public health and social problem in many Indonesian rural areas and is closely related to low reproductive health literacy, gender norms, and limited access to youth‑friendly information and services. Peer‑based approaches are increasingly recognized as effective in changing adolescents’ knowledge and attitudes regarding early marriage and reproductive health. This quantitative study aimed to analyze the effect of peer counselor training on the knowledge and attitudes of adolescent health cadres toward early marriage prevention in Village X. A quasi‑experimental one‑group pretest–posttest design was applied to 30 adolescent health cadres selected through purposive sampling. The intervention consisted of a structured peer counselor training program on reproductive health, risks of early marriage, communication skills, and basic counseling techniques. Knowledge and attitudes were measured using validated questionnaires before and four weeks after the training. Data were analyzed using paired t‑test or Wilcoxon test according to distribution assumptions. The results showed a statistically significant increase in mean knowledge and attitude scores after training, indicating improved cognitive and affective readiness of adolescent cadres to act as peer counselors. These findings support strengthening community‑based adolescent health promotion through systematic empowerment of peer counselors to prevent early marriage in rural settings.